On Conformable, Riemann-Liouville, and Caputo fractional derivatives - Guswanto, Bambang Hendriya; Andini, Leony Rhesmafiski; Triyani, Triyani (Universitas Ahmad Dahlan, 2022)
This article compares conformable fractional Derivative with Riemann-Liouville and Caputo fractional derivative by comparing solutions to fractional ordinary differential equations involving the three fractional derivatives via the numerical simulations of the solutions. The result shows that conformable fractional derivative can be used as an alternative to Riemann-Liouville and Caputo fractional derivative for order α with 1/2<α<1.